2003
DOI: 10.1002/cne.10890
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of interspecies antennal imaginal disc transplantation on organization of olfactory glomeruli and pheromone blend discrimination

Abstract: The antennal imaginal disc was transplanted between male larvae of two different heliothine moth species, Heliothis virescens (HV) and Helicoverpa zea (HZ). Males of these species respond to distinct pheromone blends, have different peripheral and central olfactory neuron specificities, as well as distinct arrangements of antennal lobe olfactory glomeruli, in the specialized male macroglomerular complex (MGC). After pupal development and adult eclosion, unilateral (with one antennal disc left intact) and bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…However, whole antennae were replaced by donor antennae. In addition, the transplantation also modified the anatomy of the recipient MGC to that of the donor MGC [43], [44]. Therefore, molecular factors responsible for the modification of behavioral preference could not be identified.…”
Section: Resultsmentioning
confidence: 99%
“…However, whole antennae were replaced by donor antennae. In addition, the transplantation also modified the anatomy of the recipient MGC to that of the donor MGC [43], [44]. Therefore, molecular factors responsible for the modification of behavioral preference could not be identified.…”
Section: Resultsmentioning
confidence: 99%
“…Tumlinson et al 1989,1994; Vickers et al 2003; Domingue et al 2007, 2008; Kanno et al 2010; El-Sayed et al 2011; Leary et al 2012; Martin et al 2013), our finding that 24% of the sampled, pheromone-responsive protocerebral neurons in this study did not distinguish among the tested stimuli (supplemental Table 1) is surprising. Pairwise comparisons of responses to different pheromonal stimuli (EEZ vs. BAL, EEZ vs. mixture, BAL vs. mixture) showed that 50–80% of neurons exhibited no significant differences in their responses to these stimulus pairs (Figure 1, bottom).…”
Section: Discussionmentioning
confidence: 52%
“…This behaviour is exhibited by normal males but has not been observed in normal females because the antennae of M. sexta females lack ORCs responsive to the main sex pheromone components (Kaissling, 1989). In interspecific antennal imaginal disc transplantation experiments between Heliothis virescens and Helicoverpa zea males, both types of unilateral transplants continued to exhibit upwind antemotactic flight in a wind tunnel to the recipient pheromone blend (Vickers et al, 2003). In contrast with our results, the interspecific transplantation of only one antenna was not sufficient to produce a behavioural change.…”
Section: Discussionmentioning
confidence: 91%